SOCIAL ADAPTATION AND PSYCHOLOGICAL ADJUSTMENT AND THEIR RELATIONSHIP TO DEFENSIVE SKILLS IN VOLLEYBALL FOR THE PREMIER LEAGUE - Qahtan Mohammed Jabbar; Munadhil Adil Kasim (Journal Park Publishing, 2023)
The present study was carried out for players in the premier league of Iraq in volleyball to find out the defensive skills level of volleyball players and its relationship with their social and psychological adaptation. In Iraq, no scientific evidence indicates the social adaptation and psychological adjustment level of premier league volleyball players. Thus, this study was planned to investigate the relationship among defensive skills, social adaptation, and psychological of Iraq's premier league club volleyball players. The study's research design encompassed 46 out of (53) premier league volleyball players from the clubs of the southern region for the excellent class by (3) clubs. The players were to choose on the bases of clubs: South Gas (n=16), Al-Bahri SC (n=15), and City of AL-Shuhadaa (n=15). Using SPSS (V.24), descriptive statistics, Pearson Product Moment correlation coefficients (Bivariate), Multiple Regression, and One-Way ANOVA were used to assess the relationship, prediction, and differences between and among the researched variables. Significant mean differences were distinguished using a P-value of less than 0.05. The results revealed that Iraq premier league volleyball players had volleyball players in the Premier League characterized by psychological compatibility and good social adaptation. The use of defensive skills tests positively impacted the performance of volleyball players in the Premier League and the existence of a significant correlation between social transformation and psychological adjustment, and defensive skills. Since position-wise social adaptation and psychological adjustment are the defensive skills in players' performance in a volleyball game, coaches should consider them during the selection and assignment of players to the proper playing positions. Due to the impact of position-specific social and psychological adaptations on the defensive skills performance of volleyball players, coaches must consider these factors when selecting and allocating players.
Keywords: Social Adjustment, Psychological Adjustment, Defensive Skills, Premier League.